Sosialisasi Perilaku Hidup Bersih dan Sehat di Desa Fulolo Kecamatan Botomuzoi Kabupaten Nias - Tri Love Gea, Tri Love Putrawan Gea; Risman Yanti Zebua, Dewi; Lase, Zonima (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The Clean and Healthy Living Behavior (PHBS) socialization activity is a form of community service that aims to raise public awareness of the importance of independent health maintenance. Activities were implemented in Fulolo Village, Botomuzoi District, Nias Regency. Methods included initial observation, direct counseling, interactive discussions, and distribution of educational materials. The results showed a significant increase in the community's understanding of PHBS practices. A reference from a similar study at SDN 01 Bantar shows that this educational approach greatly impacts the improvement of healthy behaviors, especially handwashing with soap. Therefore, this activity is important for promoting and preventing illness to achieve a healthy village in a sustainable manner.